2014
DOI: 10.1186/1472-6963-14-388
|View full text |Cite
|
Sign up to set email alerts
|

The effects of China’s New Cooperative Medical Scheme on accessibility and affordability of healthcare services: an empirical research in Liaoning Province

Abstract: BackgroundChina’s New Cooperative Medical Scheme (NCMS), launched in 2003, was intended to prevent the impoverishment due to catastrophic illness costs. Previous studies have been conducted on the “design flows” of the NCMS, for example, the irrational insurance benefit package. But after several years of implementation, very little has been known about the improvements made by the NCMS and rural residents’ attitudes toward it. This article specifically focused on the improvements of healthcare services and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The medical security system is known to have an impact on the use of inpatient services [23,31,32]. Some studies have shown that patients enrolled in NRCM are more likely to seek health care services [2,[33][34][35]. The NRCM got started in Jiangxi Province in 2003, and Wuyuan, Xiushui, and Luxi counties were randomly selected for this study to examine the impact of this new system in 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical security system is known to have an impact on the use of inpatient services [23,31,32]. Some studies have shown that patients enrolled in NRCM are more likely to seek health care services [2,[33][34][35]. The NRCM got started in Jiangxi Province in 2003, and Wuyuan, Xiushui, and Luxi counties were randomly selected for this study to examine the impact of this new system in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the less developed region is the main focus in this phase. How to improve the health level of rural residents in less developed areas and achieve equalization of medical and health services have been a major concern [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Through years of development, the security level and coverage of the scheme have been greatly increased. Although study results are inconclusive on whether the NCMS has lightened the financial burden for rural residents, the scheme has improved the situation of hard‐to‐receive healthcare services . The NCMS provides a representative model for all countries, especially for developing countries, which face fewer resources and a heavy healthcare burden.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, we can't get the same result, that could be explained that since in 2003 China introduced New Cooperative Medical Scheme, which enhanced the financing standard and reduced the burden for the low income families. 29 but the logistic regression model display age wasn't the influencing factor. But in the model we find the AOR of age over 80 is 1.81 and the AOR95%CL was 0.80-4.07 which was a wide confidence interval.…”
Section: Predictors Of Utilization Of Physical Examination Among Seasmentioning
confidence: 97%